Intensification of extraction of curcumin from Curcuma amada using ultrasound assisted approach: Effect of different operating parameters - Shirsath, S. R.; Sable, S. S.; Gaikwad, S. G.; Sonawane, S. H.; Saini, D. R.; Gogate, P. R. (Ultrasonic Sonochemistry, 2017)
Curcumin, a dietary phytochemical, has been extracted from rhizomes of Curcuma amada using ultrasound assisted extraction (UAE) and the results compared with the conventional extraction approach to establish the process intensification benefits. The effect of operating parameters such as type of solvent, extraction time, extraction temperature, solid to solvent ratio, particle size and ultrasonic power on the extraction yield have been investigated in details for the approach UAE. The maximum extraction yield as 72% was obtained in 1 h under optimized conditions of 35 degrees C temperature, solid to solvent ratio of 1:25, particle size of 0.09 mm, ultrasonic power of 250 W and ultrasound frequency of 22 kHz with ethanol as the solvent. The obtained yield was significantly higher as compared to the batch extraction where only about 62% yield was achieved in 8 h of treatment. Peleg's model was used to describe the kinetics of UAE and the model showed a good agreement with the experimental results. Overall, ultrasound has been established to be a green process for extraction of curcumin with benefits of reduction in time as compared to batch extraction and the operating temperature as compared to Soxhlet extraction.
Keywords: Acrylamide; Cavitation; Curcumin Extraction; Design; Enhancement; Functionalized Silica; kinetics; Microwave; Nanoparticles; Natural-products; Optimization; Phenolic-compounds; Process Intensification; Solid-liquid Extraction; Ultrasound

Role of base fluid on the thermal conductivity of oleic acid coated magnetite nanofluids - Lenin, Ramanujam; Joy, Pattayil Alias (COLLOIDS AND SURFACES A-PHYSICOCHEMICAL AND ENGINEERING ASPECTS, 2017)
Thermal conductivity enhancement of nanofluids of oleic acid coated magnetite nanoparticles dispersed in four different base fluids (toluene, xylene, mesitylene, kerosene) is studied to understand the role of the solvent (base fluid). From the correlation of the thermophysical properties of the base fluid with the thermal conductivity of the corresponding nanofluid, it is found that the nanofluid with the base fluid of lower intrinsic thermal conductivity and dielectric constant shows relatively larger enhancement in the thermal conductivity. A linear increase in the thermal conductivity with increasing viscosity is observed for all four nanofluids studied. The concentration dependent thermal conductivity studies showed enhancement only above a particular concentration, within the sensitivity of the measurement, and this critical concentration is different for the different nanofluids. The nanofluid with kerosene showed the lowest critical concentration for thermal conductivity enhancement compared to the other nanofluids. The difference between the experimental thermal conductivity and the calculated value using the Maxwell model is found to depend on the critical concentration. By assuming the critical concentration as the zero concentration, it is found that all the studied nanofluids almost follow the Maxwell model of thermal conductivity. Thus, for the dispersions of the same oleic acid coated magnetite nanoparticles, the base fluid affects the critical concentration for thermal conductivity enhancement, probably due to the interfacial effects arising from the surfactant-solvent interactions.
Keywords: Brownian-Motion; Enhancement; Heat-transfer Characteristics; Magnetic nanofluids; Maxwell model; Nanoparticles; Particle Migration; Size; stability; Suspension; Temprature; Thermal conductivity; Thermophysical properties; transport mechanism; viscosity

Studies on the role of unsaturation in the fatty acid surfactant molecule on the thermal conductivity of magnetite nanofluids - Lenin, Ramanujam; Joy, Pattayil Alias (Journal of colloid and interface science, 2017)
To study the role of unsaturation in the surfactant molecule on the thermal conductivity of magnetite nanofluids, four different fatty acid (stearic, oleic, linoleic, and linolenic acids with different degree of unsaturation) coated magnetite nanoparticles of comparable size are prepared and dispersed in toluene. It is found that the nanofluid with the saturated fatty acid coated nanoparticles show larger viscosity than the fluid with the unsaturated fatty acid coated particles at all concentrations. Thermal conductivity studies show enhancement only above a critical concentration for all fluids. The critical concentration for thermal conductivity enhancement varies with the surfactant, possibly due to the difference in the degree of aggregation of the nanoparticles in the fluid, because of the difference in the conformation of the surfactant molecules on the nanoparticle's surface. The experimental thermal conductivity follows the Maxwell model at higher concentrations. From the overall studies, it is observed that the thermal conductivity of the fluids with aggregated or assembled nanoparticles shows slightly larger enhancement than that of the fluids with isolated particles. However, in the presence of a magnetic field, the fluids with isolated nanoparticles showed relatively larger enhancement, possibly due to the easy response of the isolated magnetite nanoparticles to the applied field. (C) 2017 Elsevier Inc. All rights reserved.
Keywords: Chains; Dynamics; Enhancement; Fields; Fluids; Forces; gold nanoparticles; Magnetic fluid; Nanofluid; Surfactant; Unsaturation; Conformation; Thermal conductivity; Viscosity; Self-assembled Monolayers